Adsorption of Hydrogen Molecules in Nickel Decorated Silicene - Shrestha, Prajwal; Panth, Nurapathi (Himalayan Journal of Science and Technology, 2023)
First-principles simulations based on density functional theory (DFT) have been used to study the structural, electronic and magnetic properties of pristine and Ni decorated silicene sheets. Generalized Gradient Approximation (GGA) based exchange correlation functionals are used under software package Quantum ESPRESSO (QE), 6.5 versions. We have reconstructed the optimized unit cell of silicene, which has a face centered cubic (fcc) structure with two silicon atoms having lattice parameters a = b = 3.8 Å. The distance between two nearest silicene monolayers is found to be 20.5 Å which is large enough to neglect the interlayer interactions between 4×4 supercells of silicene monolayers. The atoms in the prepared supercell are fully relaxed under Bloyden-Fletcher-Goldfarb-Shanno (BFGS) scheme prior to the self-consistent, band structure and density of state (DoS) calculations. The pristine silicene is semi-metallic in nature possessing a Dirac-cone as in graphene. The h-site adsorption is found to be the most stable adsorption site of nickel in silicene with the binding energy of 4.69 eV. The addition of nickel atom completely distorts the hexagonal structure of silicene destroying the Dirac cone and the system becomes slightly insulating from its semi-metallic nature. We then construct a 4×4 nickel dimer silicene which further destroys the hexagonal silicene structure with further opening of the band gap. The charge transfer analysis in the Ni decorated systems shows the charge transfers of 0.163e and 0.294e in Ni adatom silicene and Ni dimer silicene respectively showing that the nickel atoms are adsorbed by weak van der Waals forces in both of the systems. We then proceed to hydrogen molecule adsorption in these prepared 4×4 silicene systems: pristine, Ni adatom and Ni dimer silicene systems. The adsorption energy of hydrogen in the Ni adatom silicene is found to be the largest making it the most effective system for hydrogen storage.